A Comparative Study of Environmental Awareness and Attitude of High School Students of Rural and Urban Area.: Exploring the Environmental Awareness and Attitude of High School Students in Rural and Urban Areas (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Environmentrefers to the sum total of condition and influence that affects the life anddevelopment of organism. The qualitative development and quantitative progressof mankind depends on the quality of environment. Therefore, there are no twoviews about the fact that, it is the primary responsibility of man not only topreserve the environment but also to improve it qualitatively.